2008
DOI: 10.1186/1471-2334-8-162
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of causes, clinical features and diagnosis of common zoonoses among medical practitioners in Tanzania

Abstract: Background: Many factors have been mentioned as contributing to under-diagnosis and underreporting of zoonotic diseases particularly in the sub-Sahara African region. These include poor disease surveillance coverage, poor diagnostic capacity, the geographical distribution of those most affected and lack of clear strategies to address the plight of zoonotic diseases. The current study investigates the knowledge of medical practitioners of zoonotic diseases as a potential contributing factor to their under-diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
59
0
3

Year Published

2010
2010
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 21 publications
7
59
0
3
Order By: Relevance
“…Human brucellosis is often misdiagnosed in developing countries (Paul et al, 1995) resulting in under reporting of cases. A study in Tanzania showed that medical professionals, especially those in rural areas had poor knowledge of zoonotic diseases (John et al, 2008). In areas where B. abortus is a major problem in cattle, seroprevalence rates in humans are estimated to be in the range of 1-5% (Schelling et al, 2003;Swai and Schoonman, 2009) but in areas where B. melitensis is endemic (mainly in the middle East) higher prevalence rates have to be expected (Pappas et al, 2006b).…”
Section: Epidemiology and Clinical Manifestations Of Human Brucellosismentioning
confidence: 99%
“…Human brucellosis is often misdiagnosed in developing countries (Paul et al, 1995) resulting in under reporting of cases. A study in Tanzania showed that medical professionals, especially those in rural areas had poor knowledge of zoonotic diseases (John et al, 2008). In areas where B. abortus is a major problem in cattle, seroprevalence rates in humans are estimated to be in the range of 1-5% (Schelling et al, 2003;Swai and Schoonman, 2009) but in areas where B. melitensis is endemic (mainly in the middle East) higher prevalence rates have to be expected (Pappas et al, 2006b).…”
Section: Epidemiology and Clinical Manifestations Of Human Brucellosismentioning
confidence: 99%
“…2,5 These non-specific clinical features, in addition to low clinical suspicion and inadequate diagnostic capacity, result in brucellosis often being underdiagnosed and untreated in lowresource countries. 3,6,7 Although several species of Brucella can cause human infection, B. melitensis and B. abortus are the most frequently implicated species. 8,9 B. melitensis, the more common and virulent cause of human disease, 2,10 is typically associated with sheep and goats, and B. abortus with cattle, although cross-species infections can occur.…”
Section: Introductionmentioning
confidence: 99%
“…The MOH seem to be overwhelmed by the number of diseases under their management which has made them concentrate more on those diseases that receive more financial support than those that do not or receive less support. The study also revealed lack of collaboration between the departments of health and the vector control unit [7] which may also contribute to the pitfalls in the control and management of HAT. Support from the private sector could go a long way in preventing some of the NTDs.…”
Section: Discussionmentioning
confidence: 99%
“…Cases are missed though treatment is available through WHO initiative. Lack of continued medical education for health practitioners in regions at risk of specific conditions, inadequate human resource, lack/poor diagnostic facilities and health seeking behaviours of affected communities maybe some of the contributing factors in the reduced capacity to manage HAT in endemic rural areas [3,5,6,7]. Ability of health centres to detect infected individuals is very critical in the control of HAT.…”
Section: Introductionmentioning
confidence: 99%